Advanced glycation end-products and bone fractures - Deepak Vashishth (2009)
Bone does not turn over uniformly, and becomes susceptible to post-translational modification by non-enzymatic glycation (NEG). NEG of bone causes the formation of advanced glycation end-products (AGEs) and this process is accelerated with aging, diabetes and antiresorptive postmenopausal osteoporosis therapy. Due to the elevated incidence of fracture associated with aging and diabetes, several studies have attempted to measure and evaluate AGEs as biomarkers for fracture risk. Here current methods of estimating AGEs in bone by liquid chromatography and fluorometric assay are summarized and the relationships between AGEs and fracture properties at whole bone, apparent tissue and matrix levels are discussed.